Low pre‐exercise muscle glycogen availability offsets the effect of post‐exercise cold water immersion in augmenting PGC‐1α gene expression. Issue 11 (3rd June 2019) - Allan, Robert; Sharples, Adam P.; Cocks, Matthew; Drust, Barry; Dutton, John; Dugdale, Hannah F.; Mawhinney, Chris; Clucas, Angela; Hawkins, Will; Morton, James P.; Gregson, Warren
Abstract: We assessed the effects of post‐exercise cold‐water immersion (CWI) in modulating PGC‐1α mRNA expression in response to exercise commenced with low muscle glycogen availability. In a randomized repeated‐measures design, nine recreationally active males completed an acute two‐legged high‐intensity cycling protocol (8 × 5 min at 82.5% peak power output) followed by 10 min of two‐legged post‐exercise CWI (8°C) or control conditions (CON). During each trial, one limb commenced exercise with low (LOW: <300 mmol·kg −1 dw) or very low (VLOW: <150 mmol·kg −1 dw) pre‐exercise glycogen concentration, achieved via completion of a one‐legged glycogen depletion protocol undertaken the evening prior. Exercise increased ( P < 0.05) PGC‐1α mRNA at 3 h post‐exercise. Very low muscle glycogen attenuated the increase in PGC‐1α mRNA expression compared with the LOW limbs in both the control (CON VLOW 3.6‐fold vs. CON LOW 5.6‐fold: P = 0.023, ES 1.22 Large) and CWI conditions (CWI VLOW 2.4‐fold vs. CWI LOW 8.0 fold: P = 0.019, ES 1.43 Large). Furthermore, PGC‐1α mRNA expression in the CWI‐LOW trial was not significantly different to the CON LOW limb ( P = 0.281, ES 0.67 Moderate). Data demonstrate that the previously reported effects of post‐exercise CWI on PGC‐1α mRNA expression (as regulated systemically via β‐adrenergic mediated cell signaling) are offset in those conditions in which local stressors (i.e., high‐intensity exercise and low muscle glycogen availability) have already sufficiently activated the AMPK‐PGC‐1α signaling axis. Additionally, data suggest that commencing exercise with very low muscle glycogen availability attenuates PGC‐1α signaling. Abstract : We demonstrate post‐exercise CWI does not enhance the exercise‐induced expression of PGC‐1α in muscles commencing exercise with low (i.e., <300 mmol·kg −1 dw) or very low (i.e., <150 mmol·kg −1 dw) glycogen concentrations. From a practical perspective, data suggest that the application of post‐exercise CWI as a strategic training aid for greater PGC‐1α mRNA expression is more likely to have beneficial effects when utilized after those high‐intensity training sessions that have not induced near maximal glycogen depletion.